Second opportunities for clothing products: motivations to purchase second-hand clothes - Pereira, Ana M (2023)
The second-hand clothing market is a circular economy alternative to deal with excessive consumption and reduce the  environmental impact caused by the fashion industry. In contrast to the vast research based on the US and Europe, this market is yet to be explored in Colombia, and in Latin America in general. This qualitative research explores the motivations to purchase  second-hand clothes among young consumers aged between 20 and 33 years old residing in Medellín, Colombia. Autoethnography was conducted with these consumers. Next, a pre-existing scale of second-hand shopper motivations was used in in-depth interviews to narrate their significant experiences with second-hand clothing purchases. Findings presented two profiles of second-hand clothing consumers: on the one hand, consumers passionate about design and, on the other hand, conscious professionals who are characterized by driving their purchase intentions from hedonic to economic motivations. This research offers contributions for structuring value propositions that respond to the needs of second-hand clothing buyers.